Pemanfaatan Kain Perca Menjadi Produk Bernilai Jual Tinggi Pada Ibu Rumah Tangga di Desa Plosokuning - S, Fabiani Rengganesti; Fii Ahsani, Riska; Indiana Rindianita, Seftia Bella (Edumedia Solution, 2023)
In the new normal era after the Covid-19 pandemic, people's needs in Indonesia are increasingly high, but job opportunities are also limited to college graduates and those with certain age limits. There are still quite many people who are unemployed and hope to find work to make a living. Therefore, the best solution to this problem is to create an independent economic source by utilizing waste in the surrounding environment to become handicrafts with high selling value. Many innovations have emerged in the use of waste, such as patchwork waste which can be obtained easily, and can become a craft that has value for sale. The author chose the location of Plosokuning Village as a place to carry out the community service program. Plosokuning Village is in Minomartani Subdistrict, Ngaglik District, Sleman Regency, Yogyakarta City. The average job for the people of Plosokuning Village is as farmers and vegetable seller. The aim of this community service program is to provide skills in making crafts from patchwork to increase independence and open economic opportunities for the community, especially housewives to help the family economy.